PENGAWASAN DEWAN PERWAKILAN RAJYAT DAERAH (DPRD) DALAM PROGRAM BANTUAN SOSIAL DI KABUPATEN SUMEDANG - Muhammad Farhan Nur Iman (LPPM UNSAP, 2026)
This study aims to find out how the form of supervision carried out by the Regional People's Representative Council (DPRD) of Sumedang Regency on the implementation of social assistance programs (Bansos). In addition, this study also aims to identify the inhibiting factors in the supervision process as well as the efforts made by the DPRD in overcoming these obstacles. The background of this research is based on the importance of the role of the DPRD as a legislative institution in carrying out the supervisory function of local government programs, including social assistance programs. The supervision carried out aims to ensure that the distribution of assistance runs effectively, efficiently, and on target in accordance with the provisions of laws and regulations. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out through in-depth interviews, direct observation, and documentation from various related sources. The informants consisted of members of the DPRD, local government officials, and social assistance beneficiaries. The results of the study show that the implementation of DPRD supervision of social assistance programs in Sumedang Regency has not been running optimally. This is due to several obstacles, including unclear activity standards, weak coordination between institutions, undisciplined activity schedules, and lack of socialization to the public regarding social assistance mechanisms. Despite various obstacles, the Sumedang Regency DPRD has made efforts to strengthen the supervisory function through working visit activities, development deliberative forums (Musrenbang), as well as providing recommendations and evaluations for the implementation of social assistance programs. These efforts are expected to increase transparency, accountability, and the effectiveness of social assistance programs in the future.